Effective labor taxation and the international location of headquarters - Peter Egger; Doina Maria Radulescu; Nora Strecker (Center for Economic Studies and ifo Institute (CESifo), 2012)
Profit taxes are widely acknowledged to influence the location of firms' headquarters. This paper sheds light on the role of aspects of labor taxation for the international location of headquarters. While profit taxes can be avoided in various ways, it is much harder for firms to manipulate the firm-specific labor tax base so that they may be relatively important for firm location. We construct a unique data set of effective labor taxes in 120 countries and use data on the location of 35,206 firms to analyze the impact of labor income tax rates, the progressivity of the income tax schedule, and social security contributions on firms' decisions where to locate their headquarters. The findings suggest that both a higher progressivity of the tax system and higher (employee- and employer-borne) social security contributions negatively influence a country's attractiveness for headquarters location. A one percentage point increase in a country's average labor income tax rate reduces its probability to be chosen as the headquarters location for the average firm by about 0.023 percentage points.
Keywords: H24; C25; 330; labor taxation; headquarters; location choice; nested logit; Lohnsteuer; Steuerprogression; Sozialversicherungsbeitrag; Unternehmenszentrale; Standortwahl; Standortwettbewerb; Welt